Otimização de um processo produtivo por meio do uso conjunto da teoria das restrições com programação linear: estudo de caso no segmento de plásticos descartáveis - Vieira, Egidio Carlos (2010)
The segment of disposable plastics, contextualizes itself as a market of equal resources among competing needs of different market strategies to achieve the best results are found consequently work aims at proposing the general maximization of the COMPANY X, using the concepts of the Theory of Constraints and linear programming COMPANY X has a process control of production focused on meeting the demand of sales orders. Since the demand is greater than the capacity, not always the production schedule optimizes earnings for the company. To perform the work became an exploratory research with quantitative data analysis, using the linear programming model based on qualitative concepts of the Theory of Constraints, and as a research strategy case study. By using data from COMPANY X, built a linear programming model, and using the tool SOLVER / Excel, held mock scenarios before the logic of the theory of constraints. Finally, we conclude that the gain, using the logic of Theory of Constraints, is maximized when it makes use of the tool of linear programming with use of Solver / Excel. Decision makers should have insight compared to the results proposed by the model to decrease the uncertainty of decisions. The use of these tools puts businesses in competitive advantage. However we must make every moment to compare the results generated from the model, with decisions made by assessing and consolidating the model.